BUILDING AGING COMPETENCY IN THE PROFESSIONAL WORKFORCE SERVING OLDER ADULTS. (11th November 2018) - Hinrichsen, G A; Emery-Tiburcio, E; Hyer, K
Abstract: Two Institute of Medicine (IOM; 2008, 2012) reports have underscored that the existing health and mental health workforces are woefully unprepared to meet the needs of older adults who by the year 2030 will be 20% of the U.S. population. This symposium discusses four projects that are consistent with IOM recommendations for building a more aging competent workforce. These efforts target different audiences and use different educational approaches. Hinrichsen reviews results of a survey of geropsychology specialists to identify foundational "exposure level" geropsychology knowledge competencies for generalist psychologists (based on the Pikes Peak Model for Training in Professional Geropsychology); and how they concretely inform the development of continuing education curricula. Phillips describes a program that introduces a geriatrics framework to internal medicine residents in a Dept. of Veterans Affairs healthcare system. Moye details a series of webinars ("Advancing Your Confidence as an Educator in Geriatrics and Gerontology") that builds skills in providing education and consultation for a group of webinar participants many of whom identified as specialists in their respective professions. Emery-Tiburcio outlines a free, on-line, interactive educational platform for healthcare providers, older adults, and families related to normal aging, health, dementia, and other topics. She further describes how this effort has informed development of learning activities for classroom and seminars. Hyer will provide an integrative discussion of these four presentations.